Charged functional domains introduced into a modified pectic homogalacturonan by a mixture of pectin methylesterases isozymes from sweet orange (Citrus sinensis L. Osbeck var. Pineapple). (November 2019) - Kim, Yang; Cameron, Randall G.; Williams, Martin A.K.; Lee, Chang Joo
Abstract: A mixture of multiple pectin methylesterase (PME) isozymes present in Citrus sinensis L. Osbeck were applied to demethylesterify a model homogalacturonan (HG) with 91% degree of methylesterification (DM) to 50% or 70% at pH 4.5 and 7.0, respectively. Introduced demethylesterified blocks (DMBs) were released by a limited endo polygalacturonase (EPG) digestion, separated and quantified by HPAEC. The average DMB size ( B S ¯ ) and number of such blocks per molecule ( B N ¯ ) differed depending on the degree of methylesterification and reaction pH ( P  < 0.05). A significantly larger B S ¯ was observed in HGs of 50% DM compared to 70% DMs. HG demethylesterified to 50% DM at pH 4.5 showed significantly larger B S ¯ compared to the 1 at pH 7.0 ( P  < 0.05). Degree of blockiness (DB) and absolute degree of blockiness (DBabs ), obtained using exhaustive EPG digestions, were the highest in 50% DM pH 4.5 and the lowest in 70% DM pH 7.0 displaying a similar trend with B S ¯ . However, significant difference in DB/DBabs between the pHs was only observed in 70 DM samples. The distribution of DMBs released by the limited EPG digest was predicted by mathematical modeling and compared with the experimental results. The in silico modeling of the distributions of blocks is best explained by a processive multiple attack mode of action. The results thus support a Citrus sinensis PME mixture can be applied to introduce demethylesterified blocks of designated size into pectin molecules. Graphical abstract: Image 1 Highlights: Multiple pectin methylesterases from Citrus sinensis were used to demethylesterify a homogalacturonan. Average demethylesterified block size ( B S ¯ ) and number ( B N ¯ ) differed depending on DM and pH. In silico modeled processive multiple attack mode of action of the esterases best explained block distributions. Significant correlation between B S ¯, B N ¯, absolute degree of blockiness and DM was observed. Differences in B S ¯ & B N ¯ manifested among multiple PME isozymes and three citrus isozymes.